2020
DOI: 10.1097/coc.0000000000000678
|View full text |Cite
|
Sign up to set email alerts
|

Locoregional Therapy Protocols With and Without Radioembolization for Hepatocellular Carcinoma as Bridge to Liver Transplantation

Abstract: Objective: The objective of this study was to compare posttransplant outcomes in patients undergoing bridging locoregional therapy (LRT) with Y-90 transarterial radioembolization (TARE) based protocol compared with transarterial chemoembolization based protocol for hepatocellular carcinoma (HCC) prior liver transplantation (LT). Materials and Methods: Patients listed for LT with HCC within the Milan criteria at our center who had bridging LRT were treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
18
0
1
Order By: Relevance
“…HCC patients with high-risk MVI waiting for LT may get benefit from preoperative neo-adjuvant treatment. A recent study demonstrated that bridging loco-regional therapy with Y-90 trans-arterial radio-embolization could reduce the incidence of MVI after LT and may improve tumor control and reduce post-LT recurrence ( 69 ). Nevertheless, it needs to be further verified in randomized controlled trials.…”
Section: And Surgical Outcomesmentioning
confidence: 99%
“…HCC patients with high-risk MVI waiting for LT may get benefit from preoperative neo-adjuvant treatment. A recent study demonstrated that bridging loco-regional therapy with Y-90 trans-arterial radio-embolization could reduce the incidence of MVI after LT and may improve tumor control and reduce post-LT recurrence ( 69 ). Nevertheless, it needs to be further verified in randomized controlled trials.…”
Section: And Surgical Outcomesmentioning
confidence: 99%
“…A recent retrospective study compared posttransplant outcomes in patients undergoing bridging with Y90 RE and with TACE. Not surprisingly, significantly fewer treatments allowed maintaining patients within Milan Criteria in the Y90 RE group (1.46 vs. 2.43; p = 0.001), while there was no difference in time on the transplant list between the two groups [ 75 ]. In addition, microvascular invasion at histopathology, which represents a well-established prognostic factor associated with worse disease-free survival and OS, occurred significantly less in the Y90 RE group compared with the TACE group (3.6% vs. 27%; p = 0.013) [ 75 , 76 ].…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…Not surprisingly, significantly fewer treatments allowed maintaining patients within Milan Criteria in the Y90 RE group (1.46 vs. 2.43; p = 0.001), while there was no difference in time on the transplant list between the two groups [ 75 ]. In addition, microvascular invasion at histopathology, which represents a well-established prognostic factor associated with worse disease-free survival and OS, occurred significantly less in the Y90 RE group compared with the TACE group (3.6% vs. 27%; p = 0.013) [ 75 , 76 ]. Due to the small size of the Y90 particles (30 to 60 μm), tumour cell death primarily derives from radiation delivery causing apoptosis of endothelial cells [ 77 ].…”
Section: Treatments For Bridging and Downstagingmentioning
confidence: 99%
“…Many studies have demonstrated that bridging therapies are positively correlated to encouraging posttransplant outcomes. 55,56 In clinical practice today, localized treatments such as TARE or transarterial chemoembolization (TACE) are performed as a bridge to liver transplantation. 20,21,57,58 TACE is a chemoembolization treatment that directly injects a chemotherapeutic agent into the tumor and blocks the main arterial blood flow.…”
Section: Tare As a Bridging Therapymentioning
confidence: 99%